Health Care Empowerment in Increasing Community Knowledge Regarding Family Medicine Plants (Toga) for the Prevention of Hypertension at Puskesmas Dadok Tunggul Hitam, Padang - Yuanita Ananda; Mulyanti Roberto Muliantino; Zifriyanthi Minanda Putri; Muthmainnah Muthmainnah; Edo Gusdiansyah (Warta Pengabdian Andalas)
Hypertension is often referred to as "the silent killer" because it often goes without complaints, so sufferers do not know that they have hypertension but then find that they already have a disease or complications from hypertension. Hypertension treatment or prevention can be done traditionally using Family Medicinal Plants (TOGA). TOGA is increasingly preferred because of its low side effects and is more suitable for various metabolic and degenerative diseases. An area with a high incidence of hypertension is the Dadok Tunggul Hitam Padang Community Health Center. The high incidence of hypertension in this area is because people do not comply with the diet of hypertensive patients and do not know the correct treatment methods. Thus, it is essential to educate people in the area about the treatment of hypertension using family medicinal plants. The activity was carried out on 28 July 2023 by conducting a pretest first to determine the community's understanding before providing intervention, then continuing with providing education and handing over Family Medicinal Plant (TOGA) seeds to hypertension patients and at the end of the session a posttest was carried out again. The results were that public knowledge before education was 65% and after education was 100%. There was increasing in knowledge scores because people were enthusiastic about participating in education. The suggestion for the community health center is to monitor the results of this education.